Aboveground biomass and carbon stocks in subtropical forests - Hiago Adamosky Machado; Adriane Avelhaneda Mallmann; Kauana Engel; José Augusto Spiazzi Favarin; Jordan Luis Campos Modesto; Carlos Roberto Sanquetta; Ana Paula Dalla Corte; Henrique Soares Koehler; Sylvio Péllico Netto; Alexandre Behling; Jonathan William Trautenmüller (Ecological Indicators)
Quantifying plant biomass in native forests is essential to understanding ecosystem health, primary productivity, biodiversity, and the carbon cycle, contributing to climate regulation. Therefore, the objective of this study was to establish biomass estimators and quantify biomass and carbon stocks in subtropical forests in Brazil. The study area can be considered one of the largest preserved areas of the Atlantic Forest biome, covering approximately 6,000 km2. Two procedures were used to quantify biomass and carbon: i) for trees with less than 50 cm of dbh, equations were established using allometric data collected; ii) for trees with more than 50 cm of dbh, the equations established by Trautenmüller et al. (2021) were used. These equations were biologically consistent and were corrected for heteroscedasticity, using the WNSUR procedure. These equations were later used to estimate the biomass of everyone in an inventory of subtropical forests in the state of Paraná, Brazil. A total of 456,302.00 ha of area with vegetation cover were found, with an average biomass stock of 117.26 Mg.ha−1. The total biomass stock for the entire area was 53,505.97 Gg, and the carbon equivalent was 92,208.63 Gg, highlighting the need to preserve this area with vegetation cover. One of the most immediate actions to mitigate the effects of climate change is to reduce deforestation, which can be the result of human activities or caused by mass movement. New studies should be carried out to assess the effects of climate extremes on carbon stocks and how these can affect the lives involved.